Food supplements and products for external use based on bioactive principles from whey, egg and bee by-products - Alef Ibram; Elena Lupu; Valentina Filip; Petru Sevciuc; Elena Pătruț; Viorica Chiurciu (Medicamentul Veterinar)
Bioactive principles extracted from natural sources are of great interest to medical and pharmaceutical researchers, especially those that may result from residual products remaining after industrial processing. Thus, new methods are being sought to capitalize the active compounds in the by products obtained from the processing of various products, such as whey proteins, organic calcium extracted from eggshells and propolis extracts. The present research started from the individual benefits of these products for human health, resulting in their use as raw materials for the formulation of main pharmaceutical preparations, namely, food supplements and products for external use.